2017
DOI: 10.1002/pts.2333
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of sodium bicarbonate‐incorporated LDPE films with deodorizing function for kimchi packaging

Abstract: Volatile compounds produced during the fermentation of kimchi result in a sour taste and unpleasant odor. Here, we evaluated the utility of sodium bicarbonate (baking soda) as a natural deodorant in kimchi packaging. Baking soda decomposed into sodium carbonate, which showed superior deodorizing effects at 180°C, and aroma patterns were altered after deodorizing treatment with baking soda and heat-treated baking soda. Moreover, the numbers of off-odor compounds were decreased when using baking soda or heat-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…(2009) found that processing temperatures play a major role in determining the efficiency of the investigated active films. The choices of active materials are often limited because of their low thermal stability and volatility during extrusion or injection molding or incompatibility of the component with the matrix polymer materials (Nobile et al., 2009; Jeong & Yoo, 2017). To examine the effectiveness of GSE as a filler for active deodorizing packaging materials, GSE/PCL films were prepared by melt compounding and extrusion process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(2009) found that processing temperatures play a major role in determining the efficiency of the investigated active films. The choices of active materials are often limited because of their low thermal stability and volatility during extrusion or injection molding or incompatibility of the component with the matrix polymer materials (Nobile et al., 2009; Jeong & Yoo, 2017). To examine the effectiveness of GSE as a filler for active deodorizing packaging materials, GSE/PCL films were prepared by melt compounding and extrusion process.…”
Section: Resultsmentioning
confidence: 99%
“…As the GSE content increased, their arrangement on the PCL film became increasingly irregular. These cracks and voids likely adversely affect the mechanical and barrier properties (Jeong & Yoo, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium bicarbonate is very mildly alkaline in water because of the formation of carbonic acid and hydroxyl ion. Researchers led by Yoo have studied the deodorant packaging of kimchi through bicarbonate‐incorporated low‐density polyethylene (LDPE) films.…”
Section: Introductionmentioning
confidence: 99%